Para-aortic paraganglioma and its surgical management: A Case Report - Muhammad, Faseeh; Daud, Muhammad; Ullah, Waseem; Ali, Shahzad; Mubassir, Muhammad; Ullah, Sajjad (International Journal of Pathology, 2025)
Background: Paragangliomas are rare neuroendocrine tumors arising from chromaffin cells of the autonomic nervous system. They are challenging in children due to rarity and variable presentation. Case Report We report a 15-year-old boy with headache, palpitations, sweating, and persistent hypertension. Plasma and urine catecholamines were markedly elevated. CT and MIBG imaging localized a functioning para-aortic mass. Preoperative alpha blockade followed by beta blockade was given. He underwent midline laparotomy with complete excision of a highly vascular tumor abutting the abdominal aorta. Histopathology confirmed a benign paraganglioma without malignant features. Recovery was uneventful, and both blood pressure and catecholamine levels normalized. At three months he remained asymptomatic with normal laboratory values on follow-up. Conclusion This case supports consideration of paraganglioma in adolescents with unexplained hypertension, emphasizes multidisciplinary care, and highlights the need for long-term surveillance for recurrence.